Control Plaque And Gingivitis Through Different Kinds Of Toothbrushes - Dr Rui Li; Dr Danying Tao; Prof Xiping Feng (Elsevier, 2023)
Aim or Purpose: To evaluate the effectiveness of electric toothbrushes and manual toothbrushes for plaque and gingivitis control. Materials and Methods: This study was conducted among adults (18-65 years old) with good general health in multi-center in China. Adults who had at least 20 examinable natural teeth, with a baseline examination PI score ≧ 1.5, and at least 20 gingival bleeding sites will be randomly assigned into two groups as follows: Gp1 - Brushing with sonic vibrating electric toothbrush + fluoride toothpaste;Gp2 - brushing with American Dental Association Reference manual toothbrush + fluoride toothpaste. Modified Gingival Index (MGI), Gingival Bleeding Index (GBI), and Modified Plaque Index (MPI) was assessed at baseline, 5 day, 6 week and 3 month by the same independent examiner. Results: 241 adults were included at baseline in this study, 121 in Gp1 and 120 in Gp2. At 3-months, the mean MGI decreased by 17.49% and 11.26% in Gp1 and Gp2, respectively (X2 test, P=0.1693), while the mean GBI decreased by 34.93% in Gp1 and 35.76% in Gp2 (X2 test, P=0.8709). The proportion of mean MPI decreasing in Gp1 and Gp2 was 13.58% and 7.79%, respectively (X2 test, P=0.0253). Conclusions: At 3-months, adults who receiving sonic vibrating electric toothbrush+fluoride toothpaste had a better result in plaque control than those receiving manual toothbrush+fluoride toothpaste. Longer term results will be shown in later study.